PENGARUH MACAM MEDIA DAN DOSIS URIN KELINCI TERHADAP HASIL TANAMAN SELEDRI (Apium graveolens, L.) - Anggitania Segari; Hadi Rianto; Yulia Eko Susilowati (JURNAL VIGOR, 2017)
A study on the influence of kinds of media and dose of rabbit urin on yield of celery (Apium graveolens, L.) was conducted in November 2015 until Februari 2016 in the village of Selomoyo, District Kaliangkrik Magelang Regency, altitude 710 m. The type of soil is latosol with a Ph of 6,5. The experiment was conducted using a 2 x 4 factorial arraged in a completely randomized design with three replications. The first factor is kind of media: soil: goat manure:chaff, soil: goat manure: charcoal husk, The second factor is dose of rabbit urine 0, 150, 300, 450 ml/polybag. The results showed that the kinds of media is hight significantly effect only on the number of tillers, the number of the leaves stalk and the fresh weight of the shoots. While the dose of rabbit urine hight significantly effect on the number of tillers and shoots weight of dry, and significantly effect on the number of leaves stalk, significantly effect on the number of leaves stalk. The combination of kinds of media and dose  of rabbit urine is significantly effect on the number of the leaves stalk.